Common variants in CRP and LEPR influence high sensitivity C-reactive protein levels in North Indians. - Anubha Mahajan (Public Library of Science (PLoS), 2011)
Background High sensitivity C-reactive protein (hsCRP) levels are shown to be influenced by genetic variants in Europeans; however, little is explored in Indian population. Methods Herein, we comprehensively evaluated association of all previously reported genetic determinants of hsCRP levels, including 18 cis (proximal to CRP gene) and 73 trans-acting (distal to CRP gene) variants in 4,200 North Indians of Indo-European ethnicity. First, we evaluated association of 91 variants from 12 candidate loci with hsCRP levels in 2,115 North Indians (1,042 non-diabetic subjects and 1,073 patients with type 2 diabetes). Then, cis and trans-acting variants contributing maximally to hsCRP level variation were further replicated in an independent 2,085 North Indians (1,047 patients with type 2 diabetes and 1,038 non-diabetic subjects). Results We found association of 12 variants from CRP, LEPR, IL1A, IL6, and IL6R with hsCRP levels in non-diabetic subjects. However, only rs3093059-CRP [β = 0.33, P = 9.6×10⁻⁵] and the haplotype harboring rs3093059 risk allele [β = 0.32 µg/mL, P = 1.4×10⁻⁴/P(perm) = 9.0×10⁻⁴] retained significance after correcting for multiple testing. The cis-acting variant rs3093059-CRP had maximum contribution to the variance in hsCRP levels (1.14%). Among, trans-acting variants, rs1892534-LEPR was observed to contribute maximally to hsCRP level variance (0.59%). Associations of rs3093059-CRP and rs1892534-LEPR were confirmed by replication and attained higher significance after meta-analysis [β(meta) = 0.26/0.22; P(meta) = 4.3×10⁻⁷/7.4×10⁻³ and β(meta) = -0.15/-0.12; P(meta) = 2.0×10⁻⁶/1.6×10⁻⁶ for rs3093059 and rs1892534, respectively in non-diabetic subjects and all subjects taken together]. Conclusion In conclusion, we identified rs3093059 in CRP and rs1892534 in LEPR as major cis and trans-acting contributor respectively, to the variance in hsCRP levels in North Indian population.